Transfusion practice in patients receiving VV ECMO (PROTECMO): a prospective, multicentre, observational study - Martucci, Gennaro; Schmidt, Matthieu; Agerstrand, Cara; Tabatabai, Ali; Tuzzolino, Fabio; Giani, Marco; Ramanan, Raj; Grasselli, Giacomo; Schellongowski, Peter; Riera, Jordi; Hssain, Ali Ait; Duburcq, Thibault; et al. (The Lancet. Respiratory medicine, 2023)
BACKGROUND: In patients receiving venovenous (VV) extracorporeal membrane oxygenation (ECMO) packed red blood cell (PRBC) transfusion thresholds are usually higher than in other patients who are critically ill. Available guidelines suggest a restrictive approach, but do not provide specific recommendations on the topic. The main aim of this study was, in a short timeframe, to describe the actual values of haemoglobin and the rate and the thresholds for transfusion of PRBC during VV ECMO. METHODS: PROTECMO was a multicentre, prospective, cohort study done in 41 ECMO centres in Europe, North America, Asia, and Australia. Consecutive adult patients with acute respiratory distress syndrome (ARDS) who were receiving VV ECMO were eligible for inclusion. Patients younger than 18 years, those who were not able to provide informed consent when required, and patients with an ECMO stay of less than 24 h were excluded. Our main aim was to monitor the daily haemoglobin concentration and the value at the point of PRBC transfusion, as well as the rate of transfusions. The practice in different centres was stratified by continent location and case volume per year. Adjusted estimates were calculated using marginal structural models with inverse probability weighting, accounting for baseline and time varying confounding. FINDINGS: Between Dec 1, 2018, and Feb 22, 2021, 604 patients were enrolled (431 [71%] men, 173 [29%] women; mean age 50 years [SD 13·6]; and mean haemoglobin concentration at cannulation 10·9 g/dL [2·4]). Over 7944 ECMO days, mean haemoglobin concentration was 9·1 g/dL (1·2), with lower concentrations in North America and high-volume centres. PRBC were transfused on 2432 (31%) of days on ECMO, and 504 (83%) patients received at least one PRBC unit. Overall, mean pretransfusion haemoglobin concentration was 8·1 g/dL (1·1), but varied according to the clinical rationale for transfusion. In a time-dependent Cox model, haemoglobin concentration of less than 7 g/dL was consistently associated with higher risk of death in the intensive care unit compared with other higher haemoglobin concentrations (hazard ratio [HR] 2·99 [95% CI 1·95-4·60]); PRBC transfusion was associated with lower risk of death only when transfused when haemoglobin concentration was less than 7 g/dL (HR 0·15 [0·03-0·74]), although no significant effect in reducing mortality was reported for transfusions for other haemoglobin classes (7·0-7·9 g/dL, 8·0-9·9 g/dL, or higher than 10 g/dL). INTERPRETATION: During VV ECMO, there was no universally accepted threshold for transfusion, but PRBC transfusion was invariably associated with lower mortality only when done with haemoglobin concentration of less than 7 g/dL. FUNDING: Extracorporeal Life Support Organization.
Keywords: Retrospective Studies; mimotělní membránová oxygenace; Cohort Studies; Erythrocyte Transfusion; transfuze erytrocytů; Middle Aged; mužské pohlaví; Prospective Studies; Adult; Hemoglobins; kohortové studie; ženské pohlaví; retrospektivní studie; prospektivní studie; Humans; Extracorporeal Membrane Oxygenation; lidé středního věku; hemoglobiny; dospělí; Female; lidé; Male